2022
DOI: 10.1155/2022/3428838
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Composition of Iranian Low-Salt UF-White Cheese

Abstract: In cheese, the reduction of salt is still a challenging task, as sodium chloride exerts multiple and fundamental functions. Salt favors the drainage of the residual whey; enhances the taste and the aroma profile; regulates the texture, the final pH, and the water activity; and affects the microbial growth. Hence the impact of partial replacement of NaCl by KCl on the ripening characteristics of Iranian UF (ultrafiltration) cheese during storage was monitored. To produce low-salt cheese, different mixtures of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Moreover, there were no statistical differences between these cheese variants, suggesting that reducing NaCl content by 30% and replacing it with KCl by 30% has no effect on the chemical composition of the cheese. Similar results were shown by Lavasani (2022), who indicated that salting cheese with different NaCl and KCl mixtures had no effect on moisture, dry matter, fat or total nitrogen/dry matter. Therefore, lowering the salt content is important in the modern diet strategy and should be performed on different types of cheese considering that it does not significantly affect the chemical composition.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, there were no statistical differences between these cheese variants, suggesting that reducing NaCl content by 30% and replacing it with KCl by 30% has no effect on the chemical composition of the cheese. Similar results were shown by Lavasani (2022), who indicated that salting cheese with different NaCl and KCl mixtures had no effect on moisture, dry matter, fat or total nitrogen/dry matter. Therefore, lowering the salt content is important in the modern diet strategy and should be performed on different types of cheese considering that it does not significantly affect the chemical composition.…”
Section: Resultssupporting
confidence: 88%
“…The consequences of excessive salt intake include high blood pressure, osteoporosis and cardiovascular disease (Khetra et al . 2019; Lavasani 2022). The World Health Organization (WHO) has proposed the reduction of sodium intake by 30% to align with the guideline of 2 g/day (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of cheese lipids and isolation of the FFA were executed by GC as described by Shahab Lavasani [14]. Samples were prepared as follows: anhydrous Na 2 SO 4 (4 g) was used to grind cheese (2.5 g); after this, 0.4 ml H 2 SO 4 (2.5 M) and 1.0 ml internal standard solution containing C 5:0 , C 7:0 , C 9:0 , C 13:0 , and C 17:0 (0.5 mg ml-1each) were added.…”
Section: Free Fatty Acids (Ffas)mentioning
confidence: 99%
“…Identifcation and quantifcation of the cheese samples were based on known parameters. Concentrations of diferent fatty acids were based on a standard (≥99% GC; Sigma, Steinheim, Germany) [14].…”
Section: Free Fatty Acids (Ffas)mentioning
confidence: 99%
See 1 more Smart Citation